DUSTY WARRIORS: MODERN SOLDIERS AT WAR/RICHARD HOLMES - Vreÿ, Francois (Scientia Militaria - South African Journal of Military Studies, 2011)
Richard Holmes presents some insight into the events following the controversial Allied invasion of Iraq during early 2003. The events surrounding the insurgency after the premature declaration of victory in May 2003 by the former US President George W Bush forms the backdrop to the publication. At the heart of the publication reside the experiences of one particular British unit, the 1st Battalion, The Princess of Wales Royal Regiment (1 PWRR), which deployed to Iraq during April 2004. In essence much of the narrative turns upon the personal experiences of C Company of this battalion - a focus that brings a salient human face to the action as described by the author and those involved. The publication, however, covers and provides insight into much more than the tactical events and the violent uprise that raged in the British Sector in the south of Iraq.